ANALISIS MAKNA BUSANA KEBAYA PADA UPACARA ADAT RUWATAN DESA JATI SUMBER KECAMATAN TROWULAN MOJOKERTO - Tuasikal, Safrizal Roji; Sumarah, Noorshanti; Widiyanto, Kendry (Universitas 17 Agustus 1945 Surabaya, 2017)
The problem in this research is about semiotic analysis on the use of kebaya dress in thetraditional ceremony of ruwatan village Jati Sumber District Trowulan, Mojokerto regency. Theruwatan traditional ceremony in the village of Jati Sumber is a ceremony of grateful expression of thecitizens who oblige to wear kebaya clothes, especially for women. This research uses Charles SanderPierce's semiotic theory to analyze the icon, index and symbol of the object under study. This researchuses qualitative approach (descriptive).. The meaning of this study shows that every element containedin the use of kebaya fashion in traditional ceremony ruwatan Jati Sumber village has the meaning ofsanctity for white kebaya and the meaning of eternal happiness for kebaya black. The conclusion ofthis research is the use of kebaya dress at ruwatan ceremony Jati Sumber is a form of nonverbalcommunication delivery. Simultaneously also implements the meaning and symbols of Javanesewomen's self-disclosure in maintaining the identity of Indonesian women, especially Javanese women.Namely as a form of cultural preservation of the use of kebaya clothes for traditions that have beenpassed down generations from generation to generation by the previous community to thedevelopment of modern society today.Keywords: Communication, Fashion Kebaya, ruwatan ceremony, Semiotics, Meaning